Composite Material Impact Test With Resin Matrix And Kenaf Fiber Reinforcement Using The Hand Lay Up Method - Setiawan, Ferry; Anhar, Muh; Akmal, Akmal; Wicaksono, Dhimas (Indonesian Society of Applied Science, 2023)
The purpose of this study was to obtain the results of impact testing on composite material with the arrangement of kenaf fibers in woven with volume variations of 0%, 10%, 20%, 30%, 40%, and 50%. The value obtained from impact testing with 0% fiber variation has an average energy absorption yield of 1.730623009 J and an average impact price of 0.01273547 J/mm², 10% fiber has an average absorption energy yield of 1.468150063 J and an average yield of 1.468150063 J The average impact price is 0.01080396 J/mm², 20% fiber has an average energy absorption yield of 1.730623009 J and an average impact price is 0.01273547 J/mm², 30% fiber has an average energy absorption yield of 1.214516698 J and the average yield is 1.214516698 J The average impact price is 0.008937499 J/mm², 40% fiber has an average energy absorption yield of 1.993095955 J and an average impact price is 0.01466698 J/mm², 50% fiber has an average energy absorption yield of 2.264328531 J and an average yield of 2.264328531 J Average Impact Price 0.016662952 J/mm². This composite material is made with epoxy resin as a binder and kenaf fiber as a reinforcing material. The method used is hand lay-up and specimen testing using charpy impact. After testing, a micro photo will be taken to see the best specimen fracture results.